Differences in Brand Image Perceptions of Beras Kami and Mentik Wangi Rice among Bulog Kancab Semarang Customers - Dandi Maulana; Istyakara Muslichah (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This research aims to determine consumer perceptions of the brand image of Beras Kita and Beras Mentik Wangi, especially customers of the Perum Bulog Semarang Branch Office. The research method used in this research is observation and questionnaires distributed to consumers. Observations were carried out during the internship activities, namely when participating in the bazaar and questionnaires were distributed to customers where the sample taken was 65 respondents. The six indicators used in this questionnaire are awareness, quality, CSR, social image, geographical origin, and uniqueness. The results of this research show that there is a significant difference in perception between Beras Kita and Beras Mentik Wangi where consumers have the perception that Beras Mentik Wangi has a better brand image than Beras Kita. Improvements are needed to increase consumer perceptions of Beras Kita so that in the future customers will judge that Beras Kita has a positive brand image. The results of this research show that there is a significant difference in perception between Beras Kita and Beras Mentik Wangi where consumers have the perception that Beras Mentik Wangi has a better brand image than Beras Kita. Improvements are needed to increase consumer perceptions of Beras Kita so that in the future customers will judge that Beras Kita has a positive brand image. The results of this research show that there is a significant difference in perception between Beras Kita and Beras Mentik Wangi where consumers have the perception that Beras Mentik Wangi has a better brand image than Beras Kita. Improvements are needed to increase consumer perceptions of Beras Kita so that in the future customers will judge that Beras Kita has a positive brand image.